Mengoptimalkan Hasil Panen Padi Menggunakan Metode Goal Programming Dengan Pengaplikasian Nutrisi PGPR : Studi kasus : Desa Pappungan Kecamatan Kanigoro Kabupaten Blitar - M.Ainur Rhizky; Mochamad Singgih (International Forum of Researchers and Lecturers, 2023)
Papungan’s one of the villages in Blitar Regency where most of the population are farmers and mostly cultivate rice crops. The effort was made by farmers to meet the needs of the community, but still in limited quantities. From the results of interviews with farmers in Papungan village, they complained a lot because the rice crop was still relatively low, due to the scarcity and high price of fertilizers. By making PGPR (Plant Growth Promoting Rhizobacteri) organic nutrients, it is a consortium of bacteria that actively colonize plant roots which play an important role in increasing plant growth, crop yields and land fertility. This study aims to optimize the profitability of rice farming in Pappungan Village. The results of the profit optimization calculation using the Goal Programming method. This study uses primary and secondary dta, and the purpose of this study aims to solve the problem of limited resources optimally with the Goal Programming method. Based on the results of the discussion of calculations using the goal programming method, the conclusion of the optimization of rice crops and applied using LINGO software, obtained optimal results, namely Z = 424.7647 with three goals achieved, among others, the production yield reached 27,640 Kg and the selling price of rice crop production reached Rp 18,000 / Kg with production costs required for rice crop production for per hectare of Rp 61,980,000. For the results of the goal achieved (goal) optimization of crop patterns, Papungan Village farmers are recommended to plant type B rice.